Elastic and Consolidation Settlement Analysis of Rigid Footings Relying on the “Characteristic Point” - Pantelidis, Lysandros (My University, 2023)
In the present paper, the problem of finding the location of the so-called “characteristic point” of flexible footings is revisited. As known, the settlement at the characteristic point is equal to the uniform settlement of the respective rigid footing. The cases of infinitely long strips and circular footings are studied fully analytically. For the case of rectangular footings, analytical results for flexible footings are compared against the respective 3D numerical results for rigid footings; 210 different cases were examined. As shown, the location of the characteristic point may greatly deviate from what it has been proposed in the literature in mid '50s, while it strongly depends on footing shape, as well as on the thickness and the Poisson’s ratio of the compressible medium. Apart from the elastic settlement, the characteristic point is also useful in problems involving the knowledge of the vertical stress increase in the compressible medium due to footing loading, such as the consolidation settlement. In this respect, stress influence factor curves are given for rectangular and circular footings. Finally, the applicability and limitations of the “characteristic point” concept are also discussed.
Keywords: Characteristic point; Elastic settlement analysis; Flexible footings; Rigid footings; Consolidation settlement; Stress infuence factor